Association of sleep complaints with all-cause and heart disease mortality among US adults - Wang, Qiao; Hu, Shimin; Pan, Na Clara; Zhang, Tingting; Ren, Liankun; Wang, Yuping (Frontiers in Public Health, 2023)
In contrast to the consistent U-shaped association between sleep duration and mortality, the relation of sleep quality defined by sleep disorder with mortality is not conclusive. Besides, few studies have focused on the pattern of joint effects of sleep duration and sleep quality on mortality risk. Considering the underestimated prevalence of sleep disorders and the high prevalence of self-perceived sleep problems that don’t meet the diagnostic criteria, this study extends the focus from "sleep disorder" to "sleep complaint" to determine whether sleep complaint is associated with all-cause and heart disease mortality utilizing data from five cycles of National Health and Nutrition Examination Survey (NHANES) (2005 2014) linked with the most updated 2019 National Death Index (NDI). Sleep complaint was determined by the answer 'yes' to question “Ever told doctor had trouble in sleeping?”, or with history of diagnosed sleep disorder. A total of 27 952 adult participants were included. During a median follow-up of 9.25 years (interquartile range, 6.75-11.75 years), 3948 deaths occurred and 984 were attributable to heart disease. Multivariable-adjusted model revealed that sleep complaint was significantly associated with all-cause mortality risk (HR, 1.17; 95% CI, 1.07-1.28). Subgroup analysis revealed that sleep complaint was associated with all-cause (HR,1.17; 95% CI, 1.05-1.32) and heart disease (HR, 1.24; 95% CI, 1.01-1.53) mortality among the subgroup with cardiovascular disease or tumor. Besides, sleep complaint was more strongly associated with short-term mortality than long-term mortality. The joint analysis of sleep duration and sleep complaint showed that sleep complaint mainly increased the mortality risk in those with short (<6h/day, sleep complaint HR, 1.40; 95% CI, 1.15-1.69) or recommended (6-8h/day, sleep complaint HR, 1.15; 95%CI, 1.01-1.31) sleep duration group. There were no substantial alterations in the results when further adjusting for depression. In conclusion, sleep complaint was associated with increased mortality risk, indicating a potential public benefit of monitoring and managing sleep quality among population with sleep complaint not limited to sleep disorder. Of note, persons with history of CVD or tumor may represent a high-risk group that should be targeted for more aggressive intervention of sleep problems to preventing premature all-cause and heart disease deaths.